Simultaneous Removal and Extraction of Bisphenol A and 4-tert-butylphenol From Water Samples Using Magnetic Chitosan Particles - Almakhathi, Ameen A. S.; Zeeshan, Muhammad; Shah, Jasmin; Jan, Muhammad Rasul (Frontiers in Materials, 2022)
Magnetic chitosan (MC) was used as an ecofriendly and potential adsorbent for removal of bisphenol-A and 4-tert-butylphenol from water samples. The magnetic chitosan was synthesized and characterized for functional groups, surface morphology, elemental composition and crystallinity using spectroscopic techniques. Factors influencing the uptake such as pH, mass of adsorbent, bisphenol-A & 4-tert-butylphenol concentration, contact time and temperature were examined thoroughly using aqueous solutions. Equilibrium, kinetic and thermodynamic parameters were evaluated and the results revealed that the adsorption of bisphenol-A and 4-tert-butylphenol followed pseudo-second order kinetics and Langmuir adsorption isotherm. The adsorption processes were exothermic and spontaneous. The method was found feasible for the removal and extraction of bisphenol-A and 4-tert-butylphenol in environmental water samples.The recovery of bisphenol A and 4-tert-butylphenol in tap water ranged from 95.6%-96.8% and 95.4%-101.2% and in river water from 87.6%-95.9% and 92.8%-98.2%, respectively. The results indicate that magnetic chitosan is a potential adsorbent for easy, effective removal and extraction of bisphenol-A and 4-tert-butylphenol from environmental water samples and the adsorbent material is chemically benign as well as environment friendly.